2018
DOI: 10.1186/s12860-018-0160-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP signaling in Dictyostelium promotes the translocation of the copine family of calcium-binding proteins to the plasma membrane

Abstract: BackgroundCopines are calcium-dependent phospholipid-binding proteins found in many eukaryotic organisms and are thought to be involved in signaling pathways that regulate a wide variety of cellular processes. Copines are characterized by having two C2 domains at the N-terminus accompanied by an A domain at the C-terminus. Six copine genes have been identified in the Dictyostelium genome, cpnA – cpnF.ResultsIndependent cell lines expressing CpnA, CpnB, CpnC, CpnE, or CpnF tagged with green fluorescent protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…In contrast, Cpne6, originally known as N‐copine, is specifically expressed in the hippocampus and the olfactory bulbs postnatally and has recently been shown to be required for late, mature functions such as long‐term potentiation (LTP) in the hippocampus (Burk et al, ; Reinhard et al, ). Although Copines have a high sequence homology, they differ in their sensitivities to intracellular Ca 2+ concentration (Ilacqua et al, ; P. V. Perestenko et al, ). This might lead to nuanced functional differences, despite cellular overlap of expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Cpne6, originally known as N‐copine, is specifically expressed in the hippocampus and the olfactory bulbs postnatally and has recently been shown to be required for late, mature functions such as long‐term potentiation (LTP) in the hippocampus (Burk et al, ; Reinhard et al, ). Although Copines have a high sequence homology, they differ in their sensitivities to intracellular Ca 2+ concentration (Ilacqua et al, ; P. V. Perestenko et al, ). This might lead to nuanced functional differences, despite cellular overlap of expression.…”
Section: Discussionmentioning
confidence: 99%
“…These are related to cytoskeletal rearrangements such as activitydependent alteration in spine morphology during long-term potentiation in mouse hippocampus (Reinhard et al, 2016), myofilament stability in C. elegans (Warner et al, 2013), and plant growth in Arabidopsis (Hua, Grisafi, Cheng, & Fink, 2001). Copines were also associated with signaling pathways and trafficking such as contractile vacuole function and cytokinesis in Dictyostelium in response to cAMP signaling (Damer et al, 2007;Ilacqua et al, 2018) and recycling TrkB receptors to promote BDNF-TrkB signaling in mouse hippocampus (Burk et al, 2018). From this study, we conclude that Copines exhibit differential cellular expression in the mouse retina.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our lab have shown that GFP-tagged CpnA localized to the cytosol in live Dictyostelium cells [10,15]. However, when cells were treated with a calcium ionophore in the presence of calcium, GFP-tagged CpnA was found associated with the plasma membrane and intracellular organelles.…”
Section: Introductionmentioning
confidence: 82%
“…Our studies on cpnA knockout (KO) mutants ( cpnA − ) in Dictyostelium suggest that CpnA is involved in many cellular functions including cytokinesis, adhesion, and chemotaxis, and developmental functions including aggregation, slug phototaxis and thermotaxis, culmination, and stalk cell formation [12–15]. CpnA binds to membranes in a calcium‐dependent manner and specifically binds to acidic phospholipids with strongest binding to phosphatidylserine and phosphatidylinositol phosphate [11,16]. GFP‐tagged CpnA was found in the cytoplasm in live cells but translocated to the plasma membrane in response to cAMP stimulation [16].…”
mentioning
confidence: 99%
“…CpnA binds to membranes in a calcium‐dependent manner and specifically binds to acidic phospholipids with strongest binding to phosphatidylserine and phosphatidylinositol phosphate [11,16]. GFP‐tagged CpnA was found in the cytoplasm in live cells but translocated to the plasma membrane in response to cAMP stimulation [16]. In fixed cells, CpnA localized to the plasma membrane, endosomes, lysosomes, phagosomes, and contractile vacuoles (CV) [11].…”
mentioning
confidence: 99%